A influência do sistema Faxinal no Estado Ambiental da Bacia Hidrográfica do Rio Sete Saltos - PR - Ferreira, Everaldo Skalinski (2009)
The Hydrographical Basin provides among its many potential natural features, such as, being a unit of management natural resource for easy definition. However, to diagnose the interaction between the physical and biotic aspects it is necessary to use techniques that allow this task. In this research it was used the Physical-Conservationist Diagnostic methodology - DFC, for Watershed Management DFC, developed by CIDIAT / MARNR, Venezuela and adapted for Brazil by Beltrame (1994).The Sete Saltos river hydrographical Basin, the aim of this research, covers an area of 3,821 ha, placed between Ponta Grossa and Campo Largo municipalities - PR - Brazil. Part of this basin (767 ha) is placed in a unit of Faxinal System, known as Sete Saltos de Baixo. For the development of DFC, the Sete Saltos river basin was subdivided into three sections (A, B and C), for comparison of the environmental status of each section. This methodology takes into account the definition of seven parameters: level of correspondence between the foundation vegetal coverage, declivity average, rain erositivity, soil erosive potential, draining density and hydrical balance. The calculation of these parameters required the collection of data on geology, topography, soils, land cover, rainfall data and temperature, and the use of techniques of remote sensing, digital mapping and analysis of satellite images. The study of these parameters were expressed numerically, through a descriptive function, which established the environmental status of the natural resources section of the basin, through units at risk of erosion, which enable a quantitative analysis. The parameters identified were expressed numerically, through a descriptive function, which established the risk of degradation of the section of the basin, which enables the quantitative and qualitative analysis. The section A, the anthropized, presented the same value of the section B, 41,5 units risk and section C 37,7 units risk